2017
DOI: 10.1039/c7cp02031g
|View full text |Cite
|
Sign up to set email alerts
|

On exo-cyclic aromaticity

Abstract: The domain of aromaticity spans a wide range of molecules, from polycyclic aromatic hydrocarbons, heterocycles to all-metal systems. Here, in silico we demonstrate the aromaticity in CBF, extending beyond the limit of conventional aromatic molecules. This molecule gains the magic number of six π-electrons through an unusual electronic contribution from exo-cyclic atoms. The stability of the molecule is established through density functional theory, ab initio calculations as well as molecular dynamics simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Angewandte Chemie Forschungsartikel (Figure 2) the 15 2f). Obviously,t wo Ba toms bind only one 14 N 2 or 15 N 2 in this new ring molecule.W ea lso note ag ood agreement between the observed and calculated frequencies at the B3LYP and CCSD(T) levels of theory listed in Tables 1 and S3.…”
Section: Resultsmentioning
confidence: 99%
“…Angewandte Chemie Forschungsartikel (Figure 2) the 15 2f). Obviously,t wo Ba toms bind only one 14 N 2 or 15 N 2 in this new ring molecule.W ea lso note ag ood agreement between the observed and calculated frequencies at the B3LYP and CCSD(T) levels of theory listed in Tables 1 and S3.…”
Section: Resultsmentioning
confidence: 99%
“…(Figure 2) the 15 2f). Obviously,t wo Ba toms bind only one 14 N 2 or 15 N 2 in this new ring molecule.W ea lso note ag ood agreement between the observed and calculated frequencies at the B3LYP and CCSD(T) levels of theory listed in Tables 1 and S3.…”
Section: Methodsmentioning
confidence: 98%
“…Thep roposed aromatic p-electron delocalization in the cyclic compounds A and C is supported by amolecular orbital (MO) analysis and computed nucleus-independent chemical shift (NICS) values.F igures 4a nd S14 shows typical pbonding orbitals of the cyclic p-conjugated system A,w hich consists of the 4c-2e central bonding orbital (HOMOÀ2) and two further p-bonding orbitals (HOMOÀ6and À7), to which the exo-cyclicFatoms clearly contribute.Related puckered 4membered ring aromates have previously thoroughly been analyzed. [14,15] Figure 2. Excerpts from the IR spectrum obtained using a 10 Btarget with 0.5 %F 2 in (a) 14 TheN ICS value is among the most popular aromaticity indices.…”
Section: Methodsmentioning
confidence: 99%
“…High spin organic systems can be designed using Baird's rule of 4 n electron triplet aromatics [35] . Recently it is shown that delocalized (4 n +2) π electron system can also be achieved through the back donation of electrons from the group which is exo‐cyclic to the ring [36,37] . Here, the concept of this exo‐cyclic aromaticity is categorically used to stabilize high spin systems.…”
Section: Figurementioning
confidence: 99%
“…The electron dot structure of the delocalizable π electrons are given in Figure S1 (Supporting Information) and the optimized bond lengths are given in Figure 1. This type of delocalization of the electron on the p z orbital of exo‐cyclic carbon atom can help the ring to gain (4 n +2) π electrons and impose aromaticity in the systems [36,37] …”
Section: Figurementioning
confidence: 99%